Impacts of depression subcase and case on all‐cause mortality in older people: The findings from the multi‐centre community‐based cohort study in China. (23rd August 2021) - Chen, Ruoling; Zhou, Weiju; Ma, Ying; Wan, Yuhui; Qin, Xia; Rodney, Amanda; Ni, Jindong; Thomas, Erica; Gao, Jian; Spira, Adam P.; Hu, Zhi; Copeland, John R. M.
Abstract: Objectives: It is unclear whether and to what extent depression subcases and cases in older age were associated with all‐cause mortality. Little is known about gender differences in the associations. We assess these in older Chinese. Methods: We examined a random sample of 6124 participants aged ≥60 years across five provinces in China. They were interviewed using a standard method of the GMS‐AGECAT to diagnose depression subcase and case and record sociodemographic and disease risk factors at baseline, and to follow up their vital status. We employed Cox regression models to determine all‐cause mortality in relation to depression subcases and cases, with adjustment for important variables, including social support and co‐morbidities. Results: Over the 10‐year follow‐up, 928 deaths occurred. Compared to those without depression at baseline, participants with depression subcase ( n = 196) and case ( n = 264) had increased risk of mortality; adjusted hazard ratios (HRs) were 1.46 (95% CI 1.07–2.00) and 1.45 (1.10–1.91). The adjusted HRs in men were 1.15 (0.72–1.81) and 1.85 (1.22–2.81), and in women 1.87 (1.22–2.87) and 1.22 (0.83–1.77) respectively. In participants aged ≥65 years, the adjusted HRs were 1.12 (0.68–1.84) and 1.99 (1.28–3.10) in men, and 2.06 (1.32–2.24) and 1.41 (0.94–2.10) in women. Increased HR in depression subcases was higher in women than man (ratio of HRs was 1.84, p = 0.034). Conclusions: Older people with depression subcase could have increased all‐cause mortality to a similar extent to those with depression case. More attention should be paid to subcases of depression in women to tackle gender inequalities and improve survival. Key points: This study is the first to report that there were significant impacts of depression subcase and case on all‐cause mortality in older people in China, and their impacts were stronger than those from other countries averaged levels. Older Chinese with depression subcase had a similar increase in all‐cause mortality to those with depression case. This study is the first to examine gender differences in the impact of depression subcase in older age on all‐cause mortality in low and middle‐income countries. Older women in China had a higher impact of depression subcase on all‐cause mortality than their male counterparts, which needs to be addressed for intervention.